2020
DOI: 10.1101/2020.02.03.932848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An unusual MHC molecule generates protective CD8+ T cell responses to chronic infection

Abstract: The CD8+ T cell response to the intracellular parasite Toxoplasma gondii varies dramatically between mouse strains, resulting in differences in control of the parasite. Protection in BALB/c mice can be attributed to an unusually strong and protective MHC-1 L d -restricted CD8+ T cell response directed against a peptide derived from the parasite antigen GRA6. The MHC-1 L d molecule has limited peptide binding compared to conventional MHC molecules such as K b or D b , which correlates with polymorphisms associa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…As the organism ages, however, it may become advantageous to have a more diverse, specialized T cell repertoire, particularly to fight chronic infections. In line with this notion, we recently reported that TG6 T cells are resistant to exhaustion and provide a protective response to T. gondii chronic infection, properties that are linked to limited binding of self-peptides to the restricting MHC-I molecule L d (Blanchard et al 2008;Chu et al 2016;Tsitsiklis et al 2020).…”
Section: Discussionmentioning
confidence: 68%
“…As the organism ages, however, it may become advantageous to have a more diverse, specialized T cell repertoire, particularly to fight chronic infections. In line with this notion, we recently reported that TG6 T cells are resistant to exhaustion and provide a protective response to T. gondii chronic infection, properties that are linked to limited binding of self-peptides to the restricting MHC-I molecule L d (Blanchard et al 2008;Chu et al 2016;Tsitsiklis et al 2020).…”
Section: Discussionmentioning
confidence: 68%
“…B27 and B57) with limited ability to bind peptides 7,8 . Restricted peptide binding by mouse H2-L d is correlated with resistance to CD8 T cell exhaustion during chronic infection 9 , and is controlled by amino acid polymorphisms that also correlate strongly with HIV control 7,10 . The paradoxical association between restricted peptide binding and elite control may be due to the combination of weak binding to self-peptides coupled with strong binding to particular antigenic peptides 8, 9 . However, precisely why certain MHC-I molecules favor the development of particularly potent CD8 T cell responses remain a mystery.…”
Section: Introductionmentioning
confidence: 99%